Through convergence and governance: embedding empowerment in community development interventions. (21st November 2020) - Kumar, Shubham; Kumar, Deepak; Sengupta, Keya; Giri, Tapas Kumar
Abstract: To achieve social justice, equality, and quality of life under the concerted efforts deliberated for community development, countries engage in a range of interventions focusing on participation, capacity building, and sustainability. In this study, we examine two specific characteristics of livelihood interventions, development and empowerment; their relationship; and impact on community well-being. The findings suggest that while outcomes related to development and empowerment processes have a positive but meagre impact on community well-being, there is lack of continuum between them and the relationship is conditioned by convergence and governance. Further, insights from interviews also suggest that though there are institutional voids, challenging changing context, and variations in the way mobilization and participation are employed, those that will integrate good governance and strong convergence can deliver better outcomes.